The maternal stimulations as predictor of intellectual development skills in children of six and seven years old - Capa Luque, Walter (2015)
The relationship between behavioral stimulation promotion deployed by the mother and intellectual development reached by the child is analyzed. The sample comprised 51 children of both sexes, whose ages were between 6 and 7 years were enrolled between first and second grade of primary education in a public school in Lima. An ex-post-facto correlational design was used. Scales of Infant Stimulation of Panduro and Intellectual Skills test (THM1) of Yuste were used; Both instruments were applied individually. The results of simple linear regression analysis indicated that 49% of the observed changes in the child’s intellectual development is explained by stimulation of behavioral development (R = 0.70, F = 47,446, p <0.01). Both variables are related study also loud and highly significant (p <0.001) in the group of children whose mothers had the status of married filing status. Another important finding is found that children who come from a nuclear family show a positive and highly significant relationship between the study variables.